INDONESIA’S IMMIGRATION POLICY IN MANAGING THE MOBILITY OF MICE TOURIST DELEGATES AT INTERNATIONAL CONFERENCES - Annisa Wardhani; Christina Lipuringtyas Rudatin; Anggraini, Asterina; Raden Ayu Trisnayoni; Setyawan, Heri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study examines Indonesia’s immigration policies in managing the mobility of MICE delegates attending international conferences. Delegates’ mobility is a strategic element of business tourism, influencing participant arrival efficiency, travel experience, and overall destination competitiveness. The research analyzes the effectiveness of visa-on-arrival schemes, e-visa mechanisms, conference-specific immigration facilitation, and interagency coordination that supports participant flows. Data were drawn from regulatory reviews, institutional reports, and empirical insights from event organizers. Findings indicate that responsive and integrated immigration policies significantly enhance Indonesia’s attractiveness as a MICE destination, particularly in terms of accessibility, processing time, and procedural certainty. Nevertheless, challenges remain in regulatory harmonization, technological readiness, and policy literacy among stakeholders. This study recommends strengthening event-based immigration service models to improve Indonesia’s competitiveness in the global MICE market.